Olive oils flavored by essential oils: a comparison between physicochemical and sensorial analyses to attend different consumer profiles (Research, Society and Development, 2022)
To increase the attractiveness of extra virgin olive oil to consumers, the food industry has been adding essential oils (EO) to the product. However, there is a gap about the sensory and physicochemical characteristics of olive oil after the adoption of this practice. The present study aimed to: (i) develop extra virgin olive oils flavored by EO; (ii) carry out training for evaluators; (iii) to analyze sensorially the flavored and standard oils, between trained and untrained tasters, and (iv) to evaluate the effect of EO on the oxidative stability of extra virgin olive oil. Flavored oil samples were developed using extra virgin olive oil and EO of rosemary, lemon, bay leaf and oregano (0.5% w/v). Traditional olive oil was used as a standard and all study samples were sensorially evaluated by a group of trained and untrained evaluators and characterized for acidity and peroxide index. Flavored oils showed better results for all sensory tests applied when compared to the standard. The addition of EO in olive oil demonstrated the ability to increase its oxidative stability, being able to act as a natural preservative, considering the acidity variations from 0.46 to 0.64% and the peroxide index from 9.59 to 12.16 meq/ kg in the samples (reference values up to 0.8% and 20 meq/kg, respectively). In this study, the development of new products showed potential for commercial insertion, offering versatility to traditional olive oil by adding flavor, aroma and stability, and expanding the possibility of use by different consumer profiles (professional cooks or not) for application in various gastronomic preparations.